Transcriptional corepressor SHP recruits SIRT1 histone deacetylase to inhibit LRH-1 transactivation - Chanda, Dipanjan (Oxford University Press, 2010)
Orphan nuclear receptor Small Heterodimer Partner (SHP; NR0B2) is a transcriptional corepressor of a wide variety of nuclear receptors (NRs). Here, we report that SHP recruits SIRT1, a class III histone deacetylase, in an NR-specific manner to inhibit transcriptional activity. SHP interacts and co-localizes specifically with SIRT1 in vivo and inhibition of SIRT1 activity leads to a recovery from the intrinsic repressive activity of SHP but not of DAX1. Furthermore, we observed that SIRT1 does not deacetylate SHP or LRH1. However, inhibition of either SIRT1 or SHP significantly diminished the repressive effect of SHP on LRH1 transactivity. LRH1-mediated activation of CYP7A1 and SHP gene transcription was significantly repressed by both SHP and SIRT1 whereas inhibition of SIRT1 activity by inhibitors or dominant negative SIRT1 or knockdown of SHP led to a significant release of this inhibitory effect. ChIP assays revealed that SHP recruits SIRT1 on LRH1 target gene promoters and SIRT1 deacetylated template-dependent histone H3 and H4 to inhibit transcription of LRH1 target genes. Finally, we demonstrated that inhibition of SIRT1 activity significantly reversed SHP-mediated inhibition of bile-acid synthesis by LRH1 overexpression, thereby suggesting a novel mechanism of SHP-mediated inhibition of LRH1-dependent bile-acid homeostasis via recruitment of SIRT1 histone deacetylase protein.